A Rare Type of Balanitis - Bruno Duarte (Revista da Sociedade Portuguesa de Dermatologia e Venereologia, 2020)
Syphilis is an old disease and a major public health concern, which is re-emerging in the western world. Atypical syphi- litic presentations can be challenging to diagnose. We present a 23-year-old, HIV-positive man who has sex with men who presented with a 2-week history of an asymptomatic lesion on the glans. Previous topical and systemic treatments proved unsuccessful. Physical examination demonstrated a slightly indurated, ill-defined erythematous plaque over most of the glans. Enlarged, non-tender, bilateral inguinal lymph nodes were palpable. Serological tests revealed a fourfold increase in the VDRL titre (1:8, previously 1:2). A diagnosis of syphilitic balanitis of Follmann was made and complete resolution was achieved with an intramuscular single dose of benzathine penicillin 2.4 MU.